PENGUATAN EKONOMI DESA MELALUI BUMDES AL-KHAFI SUKASARI KECAMATAN DAWUAN KABUPATEN SUBANG - Andani, Diah (Jurnal Kolaborasi Pengabdian Masyarakat Fakultas Ilmu Administrasi, 2024)
diahandani@unsub.ac.id Abstract The aim of this activity is to increase community knowledge about how to strengthen the economy through Sukasari Village-Owned Enterprises (BUMDes), Dawuan District, Subang Regency. By improving the village economy through BUMDes Al-Khafi, it is hoped that this will be able to increase village income and become an element of food security in the future. The approach method used is identifying problems, analyzing needs, conducting FGDs, and making reports. The targeted outcomes include firstly increasing community knowledge about the importance of strengthening the village economy through BUMDes.